Building bridges: challenges and pathways of Applied Social Research (Simbiótica. Revista Eletrônica, 2026)
This paper discusses applied social research in the field of Brazilian social sciences, starting from the observation of its persistent academic marginality. Revisiting Florestan Fernandes’s reflections on the separation between basic and applied research, the text seeks to reposition applied social research as a legitimate mode of scientific knowledge production. Based on a literature review and the authors’ professional experience, the article proposes a conceptual definition of applied social research centered on its intentionally practical character and on dialogue with extra-academic actors. It then examines the main challenges and methodological implications of this mode of production, highlighting the diversity of interlocutors, the mediation between scientific and external logics, the situated mobilization of theory, specific ethical dilemmas, and the distinctive temporality of applied research. Finally, the paper argues for the need to strengthen its institutional standing and to recognize it as a constitutive part of scientific practice in the social sciences.
Keywords: Applied social research; Social sciences; Knowledge application; Research methodology; Scientific production